2018
DOI: 10.5014/ajot.2018.72s1-po7004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sensory Processing Patterns on Social Skills and Problem Behaviors

Abstract: Sensory processing affects daily life activities including social participation. Numerous research studies have examined the effects of sensory processing on socialization in children with conditions, while limited research examined these effects in children from the general population including typical children. Drawing from a national sample, this study included 54 children aged 3-14, and investigated how sensory processing patterns predicted social skills and problem behaviors. This study focused on shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We also examined the relationship between sensory processing styles and interpersonal problems and found that only low registration and sensory avoidance had impacts on interpersonal problems. It appears that individuals with a high tendency of low registration are less responsive respond to external stimulation and have difficulty with interpersonal relationships [10,[29][30][31]. Also, individuals with a high tendency of sensory avoidance experience tension and anxious, maladaptive behavioral tendencies toward external stimulation and others, resulting in difficulties with interpersonal relationships [6,[11][12][13][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined the relationship between sensory processing styles and interpersonal problems and found that only low registration and sensory avoidance had impacts on interpersonal problems. It appears that individuals with a high tendency of low registration are less responsive respond to external stimulation and have difficulty with interpersonal relationships [10,[29][30][31]. Also, individuals with a high tendency of sensory avoidance experience tension and anxious, maladaptive behavioral tendencies toward external stimulation and others, resulting in difficulties with interpersonal relationships [6,[11][12][13][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory processing affects an individual's daily life activities such as social participation and social skills [8][9][10]. Specifically, individuals with sensory avoidance and sensory sensitivity styles may experience tension and anxiety, and they can show maladaptive behavioral tendencies in the relationships with others [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that children with ASD participate in a limited variety of activities (Hilton et al, 2008;LaVesser and Berg, 2011). This may be due to certain ASD characteristics like sensory processing differences (Ismael et al, 2018a(Ismael et al, , 2018b, challenging behaviors and limited social functioning (Askari et al, 2015). In addition, environmental factors, like family support and social attitudes, play an important role in children with ASD's participation (Askari, et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%